Communication of the Government Regarding the Handling of Stunting in Bejijong Village, Mojokerto Regency - Aldino, Pravinska; Rizqi, Muchamad (representamen, 2025)
Stunting is a major health issue both nationally and globally. It is a condition where a child's growth is delayed due to chronic malnutrition, making the child too short for their age. In Indonesia, stunting has become a serious problem, and efforts are necessary to prevent cases of it. Following Presidential Regulation No. 42 of 2013 concerning the National Movement for Accelerating Nutrition Improvement, measures have been put in place to prevent stunting, with the government and community working together in coordination to enhance nutritional efforts. In a different context, this research examines issues related to implementing stunting prevention policies through policy advocacy. The aim is to increase support for these policies. This advocacy is multisectoral, involving multiple parties and cooperation across various sectors and levels of government in different regions. Data were collected through interviews, surveys, and document analysis. The findings are expected to contribute valuable insights to local governments and stakeholders in developing communication, outreach, and advocacy strategies for government policies on stunting management in Bejijong Village, Mojokerto Regency.